Endoscopic Hands-Off Technique versus Conventional Technique for Conversion from an Orobiliary to a Nasobiliary Tube - Min Jae Yang; Jae Chul Hwang; Miyeon Lee; Choong-Kyun Noh; Soon Sun Kim; Byung Moo Yoo; Jin Hong Kim (Gastroenterology Research and Practice)
Background. The aim of this study was to compare the outcomes of the endoscopic hands-off technique and the conventional technique when repositioning an endoscopic nasobiliary drainage (ENBD) tube from the mouth to the nose. Methods. We conducted a retrospective cohort study of all endoscopic retrograde cholangiopancreatographies (ERCPs) performed between July 2013 and May 2015 at a single tertiary referral center. A total of 1187 ERCPs were performed during the study period. Among them, 114 patients who underwent ENBD were enrolled in this study. In those patients, we used the endoscopic hands-off technique between July 2013 and May 2014 (endoscopy group) and the conventional technique between June 2014 and May 2015 (conventional group). Results. Technical success was achieved in 100% (58/58) of the endoscopy group and 94.6% (53/56) of the conventional group (P=0.115). In the 3 cases of failed conventional technique, the endoscopic hands-off technique was then performed, and conversion of the ENBD tube was successful in all of these patients. The procedure time was significantly shorter in the endoscopy group than in the conventional group (124 s versus 149 s, P=0.001). Conclusion. The endoscopic hands-off technique was feasible and effective for oral-nasal conversion of an ENBD tube.